2003
DOI: 10.1074/jbc.m208261200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of UNC119 as a Novel Activator of SRC-type Tyrosine Kinases

Abstract: Lyn, an Src-type tyrosine kinase, is associated with the interleukin (IL)-5 receptor in eosinophils. The mechanism of its activation is unknown. Through yeast twohybrid screening we have cloned and characterized a new signaling molecule, Unc119, that associates with IL-5R␣ and Src family tyrosine kinases. Unc119 induces the catalytic activity of these kinases through interaction with Src homology 2 and 3 domains. IL-5 stimulation of eosinophils increases Unc119 association with Lyn and induces its catalytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 38 publications
1
87
0
Order By: Relevance
“…T cells are probably not the only cells that upregulate Unc119 expression under inflammatory conditions. Unc119 regulates other inflammatory cells: eosinophils and myofibroblasts (11,16). We have previously reported that an elevation of the Unc119 protein level via protein transduction protects human eosinophils from apoptosis (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T cells are probably not the only cells that upregulate Unc119 expression under inflammatory conditions. Unc119 regulates other inflammatory cells: eosinophils and myofibroblasts (11,16). We have previously reported that an elevation of the Unc119 protein level via protein transduction protects human eosinophils from apoptosis (11).…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit polyclonal anti-phospho-Crk (Tyr221) Ab was acquired from Cell Signaling Technology (Danvers, MA). The generation of the rabbit polyclonal anti-Unc119 Ab and the affinity purification was described previously (11,14,15,17). For cell culture, the following Abs were used: Armenian hamster monoclonal anti-mouse CD3 (clone 145-2C11), Syrian hamster monoclonal anti-mouse CD28 (clone 37.51), mouse monoclonal anti-human CD3 (clone OKT3), mouse monoclonal anti-human CD28 (clone CD28.2), rat monoclonal anti-mouse IL-12/IL-23 (p40 subunit; clone C17.8), rat monoclonal anti-mouse IFN-g (clone XMG1.2; all from eBioscience, San Diego, CA), and rat monoclonal anti-mouse IL-4 (clone 11B.11; National Cancer Institute Preclinical Repository).…”
Section: Absmentioning
confidence: 99%
See 1 more Smart Citation
“…A late onset conerod dystrophy is produced by mutations in HRG4 which is highly enriched at photoreceptor ribbon synapses and which appears to be associated with synaptic vesicles (Kobayashi et al, 2000). Although the function of this protein at ribbon synapses is unclear, its C. elegans orthologue, UNC119, has been shown to activate SRC tyrosine kinases (Cen et al, 2003). Xlinked congenital stationary night blindness arises from mutations in the Ca v 1.4 calcium channel (CACNA1F) found in synaptic terminals of rods and rod bipolar cells (Bech-Hansen et al, 1998).…”
Section: Relation Of Synaptic Release To the Underlying Light-evoked mentioning
confidence: 99%
“…There is indirect evidence linking human C5orf30 with immune function via its association with intracellular UNC119 (13); the latter increasing both T-cell activation by up-regulating Lck/Fyn activity and Src kinases regulating macrophages activation (14,15). There are, however, no studies of the biological functions of human C5orf30 and, in view of the genetic association with RA susceptibility and severity, we have undertaken in silico analysis and both in vitro and in vivo experiments to determine its functional activities in RA.…”
mentioning
confidence: 99%